Engineering In Situ Loose Selective Interface with Conducting Channels for Practical Ah-Level Aqueous Zinc Metal Batteries - Wang, Dongdong; Dou, Shuo; Huang, Qiongying; Li, Jiaying; Xu, Mi; Li, Jingshuai; Guo, Zhendong; Qin, Siqi; Wang, Tieyan; Yu, Haipeng; Dou, Haozhen; Chen, Zhongwei (Nano-Micro Letters, 2026)
In situ construction of highly conductive and self-repairing electrode interface with porous materials remains a grand challenge for practical aqueous batteries. Herein, loose selective interface (LSI) is in situ constructed by self-assembly of porous organic cages (POCs) for practical Ah-level aqueous zinc metal batteries. The delicate balance between hydrogen-bonding interactions of POC-POC and coordination interactions of POC–anion/cation endows LSI with loose porous structure, selective Zn2+-conducting channels and dynamic self-repairing capability. LSI obtains the high Zn2+ transfer number of 0.8, fast desolvation kinetics and homogeneous electric field distribution, which induces the dendrite-free Zn deposition along the Zn (002) plane. Meanwhile, LSI effectively confines the activity of interfacial water and enhances interfacial hydrophobicity, thus inhibiting the water-induced side reactions. Notably, Zn//Zn cells deliver the cycling life over 3200 cycles at 50 mA cm−2 and Zn//NVO full cells stably perform over 10,000 cycles at 10 A g−1. Moreover, Ah-level pouch cell with high cathode areal capacity of 7.25 mAh cm−2 and limited N/P of 2.65 delivers the initial discharge capacity of 1 Ah and cycling stability for over 237 cycles. This study offers a novel methodology for constructing stable highly conductive interfaces with porous materials. Highlights: 1 A loose selective interface (LSI) is in situ constructed by self-assembly of porous organic cages for aqueous Zn metal batteries. 2 The porous LSI enables fast Zn2+ transport, dynamic self-repairing capability and dendrite-free Zn deposition. 3 Ah-level aqueous Zn pouch cells deliver 1 Ah capacity with stable cycling performance.